Polarized organic light-emitting device based on two-dimensional elliptical metal nano-column lattice structured electrode and preparation method of polarized organic light-emitting device

By integrating a two-dimensional elliptical metal nanocolumn lattice structured electrode with ITO, a composite electrode is designed as the anode of the OLEDs device, which solves the problem of non-polarized light emission of the OLEDs device, realizes the polarization control of the device and improves the light extraction efficiency, and is suitable for the display and lighting fields.

CN120640942APending Publication Date: 2025-09-12JILIN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510833359.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-20
Publication Date
2025-09-12

AI Technical Summary

Technical Problem

Existing OLEDs devices have non-polarization characteristics in light emission, resulting in high energy loss and low efficiency. Existing materials and methods are difficult to meet commercialization needs.

Method used

A two-dimensional elliptical metal nanocolumn lattice structured electrode is integrated with ITO, and a composite electrode is designed as the anode of the OLEDs device. The cavity mode is regulated by the micro-nanostructure metasurface to achieve non-radiative mode coupling emission inside the device, thereby improving the light extraction efficiency.

Benefits of technology

Without the need for external optical components and polarized light material restrictions, the polarized light emission and light extraction efficiency of OLEDs devices are improved, the device performance is optimized, and it is suitable for display and lighting fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120640942A_ABST
    Figure CN120640942A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of photoelectric devices, and particularly discloses a polarized organic light-emitting device based on a two-dimensional elliptical metal nanorod lattice structured electrode and a preparation method thereof, and the preparation method comprises the steps: carrying out the ultrasonic cleaning of a substrate through a cleaning agent, and carrying out the hydrophilic treatment for later use; preparing a two-dimensional elliptical metal nano-column dot matrix electrode by using an electron beam lithography system; and depositing the two-dimensional elliptical dot matrix electrode on a sample through vacuum thermal evaporation to complete the preparation of the whole device. According to the polarized organic light-emitting device based on the two-dimensional elliptical metal nanorod lattice structured electrode and the preparation method thereof, the cavity mode of the OLEDs device is directly regulated and controlled through the design of the micro-nano structure metasurface, so that the polarization regulation and control of the OLEDs device are realized, and the light extraction efficiency of the OLEDs device is improved; therefore, polarized light emission of the OLEDs device in the fields of display, illumination and the like is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of optoelectronic devices, and in particular to a polarized organic electroluminescent device based on a two-dimensional elliptical metal nanocolumn lattice structured electrode and a preparation method thereof. Background Art

[0002] Organic light-emitting diodes (OLEDs), as the most competitive candidates for next-generation flat-panel displays and solid-state lighting sources, typically exhibit unpolarized light emission characteristics. With the rapid development of immersive visual technology and optical communication technology, the demand for polarization of OLEDs' light emission has increased rapidly. A simple strategy is to filter with polarization optical elements attached to the outside of the device, which can selectively transmit the desired polarization component, but will result in about 50% energy loss. Achieving polarized emission directly from OLEDs can greatly simplify the device architecture while eliminating the power loss caused by the use of external optical elements. In addition, the photons trapped inside the OLEDs can be decoupled by controlling the optical modes inside the device, thereby greatly improving the external quantum efficiency of OLEDs.

[0003] Uniaxially oriented materials such as organic single crystals and chiral luminophores, as well as various processing methods such as mechanical friction and stretching to uniaxially align the luminescent molecules, have been applied to OLEDs to achieve intrinsic polarized luminescence. However, the selection of luminescent materials is limited, and the efficiency and stability of OLED devices cannot meet the needs of commercialization. Integrating optical structures with light sources can achieve effective manipulation of emitted photons from devices. Existing technologies have achieved high-efficiency and ultra-high polarization ratio linearly polarized white light emitting devices by using integrated dielectric nanogratings. Highly polarized emission is achieved by embedding photonic crystal structures within the LED structure to form a high-diffraction optical medium. Among various optical structures, artificial optical metasurfaces based on subwavelength micro-nanostructures provide unprecedented flexibility for photon manipulation in light-emitting devices by controlling the phase, intensity and polarization of light waves. Summary of the Invention

[0004] The present invention aims to provide a polarized organic electroluminescent device based on a two-dimensional elliptical metal nanopillar lattice structured electrode and its preparation method. By integrating a two-dimensional elliptical metal nanopillar lattice structure with ITO, a composite electrode is designed as the anode of an OLED device, simultaneously achieving polarization control of the OLED device and improving the light extraction efficiency of the OLED device. The cavity mode of the OLED device is directly controlled by the design of a micro-nanostructured metasurface, achieving polarized light emission from the OLED device in fields such as display and lighting without the need for additional external optical components and without being restricted by polarized light materials. The two-dimensional elliptical metal nanopillar lattice structure excites the non-radiative mode within the device through coupled emission, improving the device's light extraction efficiency and optimizing its performance.

[0005] To achieve the above objectives, the present invention provides a method for preparing a polarized OLED device based on a two-dimensional elliptical metal nanorod lattice structured electrode, comprising the following steps:

[0006] S1. Substrate pretreatment: After the substrate is ultrasonically cleaned with a detergent, the surface is wiped with a cotton ball. The solvent on the surface is removed using high-pressure nitrogen and an oven. The cleaned substrate is then placed in an oxygen plasma cleaner for hydrophilic treatment before use.

[0007] S2. Preparation of an elliptical metal nanopillar lattice electrode: uniformly spin-coating an electron beam resist on a substrate surface, using an electron beam lithography system to prepare a two-dimensional elliptical metal nanopillar lattice structure, treating the two-dimensional elliptical metal nanopillar lattice structure with a developer and a fixer, and then evaporating a metal film using a vacuum thermal evaporation process. Residual electron beam resist is removed to obtain a two-dimensional elliptical metal nanopillar lattice electrode;

[0008] S3. Place the two-dimensional elliptical metal nanocolumn lattice electrode obtained in step S2 into a vacuum evaporator, and sequentially deposit the hole injection layer, hole transport layer, light-emitting layer, electron transport layer, and cathode on the sample by vacuum thermal evaporation to complete the preparation of the polarized organic electroluminescent device based on the two-dimensional elliptical metal nanocolumn lattice structured electrode.

[0009] Preferably, in step S1, the substrate is an ITO-glass substrate, the cleaning agents are acetone, ethanol and isopropanol, the ultrasonic cleaning time is 10-30 minutes, and the oxygen plasma treatment time is 3 minutes.

[0010] Preferably, in step S2, the electron beam resist is polymethyl methacrylate (PMMA), and the heating curing temperature is 150° C. and the curing time is 3 minutes.

[0011] Preferably, in step S2, the two-dimensional elliptical metal nanorod lattice structure prepared by the electron beam lithography system has a period of 310 nm, a short axis radius fixed at 30 nm, and long axis radii of 45, 60, 75, and 100 nm, respectively.

[0012] Preferably, in step S2, the developer is a mixed solution of methyl isobutyl ketone (MIBK): isopropyl alcohol (IPA) in a volume ratio of 1:2, the fixing solution is an isopropyl alcohol (IPA) solution, the developing time is 3 minutes, the fixing time is 1 minute, and the residual electron beam resist is removed using acetone solution for 20 minutes.

[0013] Preferably, in step S3, the hole transport layer is one of 4,4'-cyclohexylbis[N,N-di(4-methylphenyl)aniline] (TAPC) and N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine (NPB), the electron transport layer is one of 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi), 4,7-diphenyl-1,10-phenanthroline (BPhen), and 3,3'-[5'-[3-(3-pyridyl)phenyl][1,1':3',1"-terphenyl]-3,3"-diyl]dipyridine (TmPyPB), the hole injection layer is MoO3, and the cathode is a composite electrode of Ca and Ag.

[0014] Preferably, in step S3, the light-emitting layer is a red organic light-emitting material and a main material, the red organic light-emitting material is bis(2-methyldibenzo[F,H]quinoxaline)(acetylacetonate)iridium(III) (Ir(MDQ)2(acac)), the main material is 4,4'-bis(N-carbazole)-1,1'-biphenyl (CBP), 1,3-bis(N-carbazolyl)benzene, and the red organic light-emitting material is doped in the main material at a mass ratio of 8% to prepare an organic phosphorescent film as the light-emitting layer.

[0015] The present invention also provides a polarized organic electroluminescent device based on a two-dimensional elliptical metal nanocolumn lattice structured electrode, which is prepared according to a preparation method of a polarized organic electroluminescent device based on a two-dimensional elliptical metal nanocolumn lattice structured electrode.

[0016] The advantages and beneficial effects of the polarized organic electroluminescent device based on the two-dimensional elliptical metal nanorod lattice structured electrode and the preparation method thereof are as follows:

[0017] The present invention's method for preparing an OLED device utilizes a two-dimensional elliptical metal nanopillar lattice as the device's anode. This method simultaneously achieves polarization control of the OLED device's light emission and improves light extraction efficiency, without requiring additional external optical components or limitations imposed by polarized light materials. This method addresses the issue of unpolarized light emission in conventional OLED devices by directly controlling the device's cavity mode through the design of a micro-nanostructured metasurface, achieving polarization control of the emitted photons and thus enabling polarized light emission in fields such as display and lighting. Furthermore, this method stimulates coupled emission of non-radiative modes within the device, improving light extraction efficiency and optimizing device performance, promising broad application prospects.

[0018] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1This is a flow chart for preparing a polarized OLED device based on a two-dimensional elliptical metal nanorod lattice structured electrode according to the present invention;

[0020] Figure 2 Scanning electron microscope images of two-dimensional elliptical metal nanorod lattice structures with different aspect ratios of Examples 1 and 2 of the present invention, wherein (a) is Example 1 and (b) is Example 2;

[0021] Figure 3 The photoluminescence (PL) and electroluminescence (EL) polarization spectra of Example 1 of the present invention, wherein (a) is the PL polarization spectrum and (b) is the EL polarization spectrum;

[0022] Figure 4 PL and EL polarization spectra of Example 2 of the present invention, wherein (a) is the PL polarization spectrum and (b) is the EL polarization spectrum;

[0023] Figure 5 These are performance graphs of Example 1, Example 2, and the reference OLEDs device of the present invention, wherein (a) is a current density-voltage relationship graph, (b) is a brightness-current density relationship graph, and (c) is a current efficiency-current density relationship graph. DETAILED DESCRIPTION

[0024] The technical solution of the present invention is further described below with reference to the accompanying drawings and embodiments.

[0025] Unless otherwise defined, technical or scientific terms used in the present invention shall have the same meaning as commonly understood by one of ordinary skill in the art to which the present invention belongs.

[0026] Unless otherwise defined, the reagents, equipment and other materials used in the present invention are all commercially available.

[0027] Example 1

[0028] A two-dimensional elliptical metal nanopillar lattice structured electrode was fabricated using electron beam lithography. The elliptical metal nanopillar lattice has a period of 310 nm, a minor axis radius of 30 nm, and a major axis radius of 60 nm. This electrode, used as the anode in an organic light-emitting diode (OLED) device, selectively amplifies the TM mode while effectively extracting photons bound to the surface plasmon mode within the device, enabling polarization control and improving the light extraction capability of the OLED device. The electroluminescence of this OLED device reaches a maximum polarization ratio of 2.0 in the red wavelength band.

[0029] Preparation method of polarized OLEDs device based on two-dimensional elliptical metal nanorod lattice structured electrode, such as Figure 1 As shown, the following steps are included:

[0030] (1) Pretreatment of ITO-glass substrate:

[0031] First, an ITO-glass substrate with a size of 2.0 cm × 1.8 cm was ultrasonically cleaned with acetone, ethanol, and deionized water for 30 minutes. The surface was then wiped and dried with acetone and ethanol in sequence. The drying process included nitrogen drying and oven drying. Finally, the dried substrate was subjected to oxygen plasma hydrophilization treatment for 3 minutes.

[0032] (2) Preparation and morphology characterization of two-dimensional elliptical metal nanopillar lattice structured electrodes:

[0033] First, a positive electron beam resist polymethyl methacrylate (PMMA) was evenly spin-coated on the substrate treated in step (1) at a speed of 6000 rpm and cured on a hot plate at 150°C for 3 minutes. Then, an electron beam lithography system was used to prepare a two-dimensional elliptical lattice with a period of 310 nm, wherein the short axis radius was 30 nm and the long axis radius was 60 nm. The sample was developed and fixed using a mixed solution of methyl isobutyl ketone (MIBK): isopropyl alcohol (IPA) with a volume ratio of 1:2 and IPA, and the sample was dried using a nitrogen gun. The obtained sample with a two-dimensional elliptical metal nanocolumn lattice structure was covered with an organic layer mask and placed in a vacuum coating apparatus with a vacuum degree of 5×10 -4 Pa, evaporated Ag electrode, thickness 35nm, deposition rate The PMMA that has not been exposed to the electron beam is removed by the metal lift-off process to obtain the Ag elliptical metal nanocolumn lattice electrode.

[0034] (3) Preparation of polarized OLEDs based on two-dimensional elliptical metal nanorod lattice structured electrodes:

[0035] The sample with the two-dimensional elliptical metal nanorod lattice structured electrode prepared in step (2) was placed in a vacuum coating apparatus and the vacuum degree was set to 5×10 -4 After Pa, a hole injection layer, a hole transport layer, a light-emitting layer, an electron transport layer and a metal cathode were sequentially deposited. The red light-emitting layer was 4,4'-bis(N-carbazole)-1,1'-biphenyl (CBP) and 8% wt bis(2-methyldibenzo[F,H]quinoxaline)(acetylacetonate)iridium(III) (Ir(MDQ)2(acac)). The thickness of the light-emitting layer was 20 nm and the deposition rate was 20%. The hole injection layer is MoO3 with a thickness of 5nm and a deposition rate of The hole transport layer and electron transport layer were N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine (NPB) and 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi), with thicknesses of 40 nm and 35 nm, respectively, and the deposition rate was The composite cathode is Ca / Ag with thickness of 3nm and 80nm respectively, and the deposition rates are and The device preparation flow chart is as follows Figure 1 As shown, the preparation of the polarized OLEDs device based on the two-dimensional elliptical metal nanocolumn lattice structured electrode was completed, and then the polarized luminescence spectrum and electroluminescence performance of the device were tested.

[0036] Figure 2 This is the SEM image of the prepared two-dimensional elliptical metal nanocolumn lattice structured electrode. It can be seen from the figure that the prepared two-dimensional elliptical metal nanocolumn lattice structure has a good morphology under a scanning electron microscope, is uniform over a large area, and has good symmetry and consistency.

[0037] Next, excitation light with a wavelength of 400 nm was perpendicularly incident on the sample surface, and a linear polarizer was placed between the light detector and the sample. By rotating the linear polarizer, angle-resolved polarized PL spectra were obtained. The maximum and minimum intensities of the polarized PL correspond to TM polarization and TE polarization, respectively. The polarized EL spectrum of the device was measured using the same method. Comparing the intensities of the TM and TE polarized EL spectra revealed that the TM / TE polarization ratio of the device was 2.0 at the peak wavelength of 609 nm.

[0038] The maximum brightness of the polarized OLEDs device based on the two-dimensional elliptical metal nanocolumn lattice structured electrode is increased from 13730 cd / m 2 Increased to 2180cd / m 2 The two-dimensional elliptical metal nanocolumn lattice structured electrode increased by 46.7%, and the light extraction ability of OLEDs devices was improved.

[0039] Figure 3 These are the PL and EL polarization spectra of Example 1 of the polarized organic electroluminescent device based on the two-dimensional elliptical metal nanocolumn lattice structured electrode of the present invention, wherein the period of the two-dimensional periodic elliptical lattice is selected to be 310 nm, the short axis radius is 30 nm, and the long axis radius is 60 nm.

[0040] Depend on Figure 3The introduction of two-dimensional elliptical metal nanopillar lattice electrodes reveals significant differences in the PL and EL emission characteristics of OLED devices under transverse magnetic (TM) and transverse electric (TE) polarization modes, respectively. The TM mode exhibits higher PL and EL emission intensities than the TE mode within the corresponding wavelength range. The consistent differential regulation of emission characteristics across different polarization modes under both PL and EL excitation modes strongly demonstrates the significant polarization control effect of the elliptical lattice structure on OLED devices. The OLED device based on a two-dimensional elliptical metal nanopillar lattice electrode with a minor axis radius of 30nm and a major axis radius of 60nm achieves a maximum polarization ratio of 2.0 in the red wavelength band.

[0041] Example 2

[0042] A two-dimensional elliptical metal nanopillar lattice structured electrode was fabricated by electron beam lithography. The elliptical metal nanopillar lattice has a period of 310 nm, a minor axis radius of 30 nm, and a major axis radius of 100 nm. This electrode, used as the anode in an OLED device, selectively amplifies the transverse magnetic polarization mode and effectively extracts photons bound to the surface plasmon mode within the device, enabling polarization control and improving the light extraction capability of the OLED device. The electroluminescence of this OLED device reaches a maximum polarization ratio of 3.2 in the red wavelength band.

[0043] A method for preparing a polarized OLED device based on a two-dimensional elliptical metal nanocolumn lattice structured electrode comprises the following steps:

[0044] (1) Pretreatment of ITO-glass substrate:

[0045] First, an ITO-glass substrate with a size of 2.0 cm × 1.8 cm was ultrasonically cleaned with acetone, ethanol, and deionized water for 30 minutes. The surface was then wiped and dried with acetone and ethanol in sequence. The drying process included nitrogen drying and oven drying. Finally, the dried substrate was subjected to oxygen plasma hydrophilization treatment for 3 minutes.

[0046] (2) Preparation and morphology characterization of two-dimensional elliptical metal nanopillar lattice structured electrodes:

[0047] First, a positive electron beam resist polymethyl methacrylate (PMMA) was evenly spin-coated on the substrate treated in step (1) at a speed of 6000 rpm and cured on a hot plate at 150°C for 3 minutes. Then, an electron beam lithography system was used to prepare a two-dimensional elliptical metal nanocolumn lattice with a period of 310 nm, wherein the short axis radius was 30 nm and the long axis radius was 100 nm. The sample was developed and fixed using a mixed solution of methyl isobutyl ketone (MIBK):isopropyl alcohol (IPA) and IPA, and dried using a nitrogen gun. The obtained sample with a two-dimensional elliptical metal nanocolumn lattice structure was covered with an organic layer mask and placed in a vacuum coating apparatus with a vacuum degree of 5×10 -4 Pa, evaporated Ag electrode, thickness 35nm, deposition rate The PMMA that has not been exposed to the electron beam is removed by the metal lift-off process to obtain the Ag elliptical metal nanocolumn lattice electrode.

[0048] (3) Preparation of polarized OLEDs based on two-dimensional elliptical metal nanorod lattice structured electrodes:

[0049] The sample with the two-dimensional elliptical metal nanorod lattice structured electrode prepared in step (2) was placed in a vacuum coating apparatus and the vacuum degree was set to 5×10 -4 After Pa, the hole injection layer, hole transport layer, light-emitting layer, electron transport layer and metal cathode were sequentially deposited. The red light-emitting layer was 4,4'-bis(N-carbazole)-1,1'-biphenyl (CBP) and 8% wt bis(2-methyldibenzo[F,H]quinoxaline)(acetylacetonate)iridium(III) (Ir(MDQ)2(acac)). The thickness of the light-emitting layer was 20 nm and the deposition rate was 20%. The hole injection layer is MoO3 with a thickness of 5nm and a deposition rate of The hole transport layer and electron transport layer were N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine (NPB) and 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi), with thicknesses of 40 nm and 35 nm, respectively, and the deposition rate was The composite cathode is Ca / Ag with thickness of 3nm and 80nm respectively, and the deposition rates are and Complete the preparation of polarized OLEDs devices based on two-dimensional elliptical metal nanocolumn lattice structured electrodes.

[0050] Next, excitation light with a wavelength of 400 nm was perpendicularly incident on the sample surface, and a linear polarizer was placed between the light detector and the sample. By rotating the linear polarizer, angle-resolved polarized PL spectra were obtained. The maximum and minimum intensities of the polarized PL correspond to TM polarization and TE polarization, respectively. The polarized EL spectrum of the device was measured using the same method. Comparing the intensities of the TM and TE polarized EL spectra revealed that the TM / TE polarization ratio of the device was 3.2 at a peak wavelength of 609 nm.

[0051] The maximum brightness of the polarized OLEDs device based on the two-dimensional elliptical metal nanocolumn lattice structured electrode is increased from 13730 cd / m 2 Increased to 21120cd / m 2 The two-dimensional elliptical metal nanocolumn lattice structured electrode increased by 53.8%, and the light extraction ability of OLEDs devices was improved.

[0052] Figure 4 These are the PL and EL polarization spectra of Example 2 of the polarized OLEDs device based on the two-dimensional elliptical metal nanocolumn lattice structured electrode of the present invention, wherein the two-dimensional elliptical metal nanocolumn lattice period is selected to be 310nm, the short axis radius is 30nm, and the long axis radius is 100nm; the OLEDs device with the two-dimensional elliptical metal nanocolumn lattice electrode has a maximum polarization ratio of 3.2 in the red light band.

[0053] Depend on Figure 3 and Figure 4 It can be seen that as the asymmetry of the two-dimensional elliptical metal nanocolumn lattice increases, the polarization ratio of the OLEDs device increases significantly with the increase of the length-short axis ratio of the structure, proving the customizable polarization control of OLEDs by the elliptical nanocolumn lattice.

[0054] Depend on Figure 5 It can be seen that the maximum brightness of the OLED device based on the two-dimensional elliptical metal nanorod array electrode with a short axis radius of 30nm and a long axis radius of 60nm is 20050cd / m 2 , compared to the maximum brightness of the reference device 13730cd / m 2 , an increase of 46%. By balancing photon extraction and charge transport, the maximum current efficiency of OLEDs devices based on a two-dimensional elliptical metal nanopillar lattice structure is increased to 12.07cd / A compared to 11.68cd / A of a planar device. The maximum brightness of OLEDs devices based on a two-dimensional elliptical metal nanopillar lattice electrode with a short axis radius of 30nm and a long axis radius of 100nm is 21120cd / m 2 , which is 53% higher than the reference device, with a maximum current efficiency of 11.85cd / A.

[0055] Example 3

[0056] A method for preparing a polarized OLED device based on a two-dimensional elliptical metal nanocolumn lattice structured electrode comprises the following steps:

[0057] (1) Pretreatment of ITO-glass substrate:

[0058] First, an ITO-glass substrate with a size of 2.0 cm × 1.8 cm was ultrasonically cleaned with acetone, ethanol, and deionized water for 30 minutes. The surface was then wiped and dried with acetone and ethanol in sequence. The drying process included nitrogen drying and oven drying. Finally, the dried substrate was subjected to oxygen plasma hydrophilization treatment for 3 minutes.

[0059] (2) Preparation and morphology characterization of two-dimensional elliptical metal nanopillar lattice structured electrodes:

[0060] First, a positive electron beam resist polymethyl methacrylate (PMMA) was evenly spin-coated on the substrate treated in step (1) at a speed of 6000 rpm and cured on a hot plate at 150°C for 3 minutes. Then, an electron beam lithography system was used to prepare a two-dimensional elliptical metal nanocolumn lattice with a period of 310 nm, wherein the short axis radius was 30 nm and the long axis radius was 100 nm. The sample was developed and fixed using a mixed solution of methyl isobutyl ketone (MIBK): isopropyl alcohol (IPA) with a volume ratio of 1:2 and IPA, and the sample was dried using a nitrogen gun. The obtained sample with a two-dimensional elliptical metal nanocolumn lattice structure was covered with an organic layer mask and placed in a vacuum coating apparatus with a vacuum degree of 5×10 -4 Pa, evaporated Ag electrode, thickness 35nm, deposition rate The PMMA that has not been exposed to the electron beam is removed by the metal lift-off process to obtain the Ag elliptical metal nanocolumn lattice electrode.

[0061] (3) Preparation of polarized OLEDs based on two-dimensional elliptical metal nanorod lattice structured electrodes:

[0062] The sample with the two-dimensional elliptical metal nanorod lattice structured electrode prepared in step (2) was placed in a vacuum coating apparatus and the vacuum degree was set to 5×10 -4 After Pa, the hole injection layer, hole transport layer, light-emitting layer, electron transport layer and metal cathode were sequentially evaporated. The red light-emitting layer was 1,3-bis(N-carbazolyl)benzene and 8% wt bis(2-methyldibenzo[F,H]quinoxaline)(acetylacetonate)iridium(III) (Ir(MDQ)2(acac)). The thickness of the light-emitting layer was 20 nm and the deposition rate was 20%. The hole injection layer is MoO3 with a thickness of 5nm and a deposition rate of The hole transport layer and electron transport layer are 4,4'-cyclohexylbis[N,N-di(4-methylphenyl)aniline] (TAPC) and 4,7-diphenyl-1,10-phenanthroline (BPhen), with thicknesses of 40 nm and 35 nm, respectively, and the deposition rate is The composite cathode is Ca / Ag with thickness of 3nm and 80nm respectively, and the deposition rates are and Complete the preparation of polarized OLEDs devices based on two-dimensional elliptical lattice structured electrodes.

[0063] Therefore, the present invention utilizes the aforementioned polarized OLED device based on a two-dimensional elliptical metal nanopillar lattice structured electrode and its preparation method. By integrating the two-dimensional elliptical metal nanopillar lattice structure with ITO and designing a composite electrode as the OLED anode, the polarization control of the OLED device and the improvement of the light extraction efficiency of the OLED device are simultaneously achieved. Through the design of a micro-nanostructured metasurface, the cavity mode of the OLED device is directly controlled, without the need for additional external optical components and without being restricted by polarized light materials, to achieve polarized light emission from the OLED device in fields such as display and lighting. The two-dimensional elliptical metal nanopillar lattice structure excites the non-radiative mode within the device to couple and emit light, thereby improving the device's light extraction efficiency and optimizing its performance.

[0064] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the same. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solutions of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.

Claims

1. A method for preparing a polarized organic electroluminescent device based on a two-dimensional elliptical metal nanorod lattice structured electrode, characterized in that: The steps include: S1. Substrate pretreatment: After the substrate is ultrasonically cleaned with a detergent, the surface is wiped with a cotton ball. The solvent on the surface is removed using high-pressure nitrogen and an oven. The cleaned substrate is then placed in an oxygen plasma cleaner for hydrophilic treatment before use. S2. Preparation of an elliptical metal nanopillar lattice electrode: uniformly spin-coating an electron beam resist on a substrate surface, using an electron beam lithography system to prepare a two-dimensional elliptical metal nanopillar lattice structure, treating the two-dimensional elliptical metal nanopillar lattice structure with a developer and a fixer, and then evaporating a metal film using a vacuum thermal evaporation process. Residual electron beam resist is removed to obtain a two-dimensional elliptical metal nanopillar lattice electrode; S3. Place the two-dimensional elliptical metal nanocolumn lattice electrode obtained in step S2 into a vacuum evaporator, and sequentially deposit the hole injection layer, hole transport layer, light-emitting layer, electron transport layer, and cathode on the sample by vacuum thermal evaporation to complete the preparation of the polarized organic electroluminescent device based on the two-dimensional elliptical metal nanocolumn lattice structured electrode.

2. The method for preparing a polarized organic electroluminescent device based on a two-dimensional elliptical metal nanorod lattice structured electrode according to claim 1, characterized in that: In step S1, the substrate is an ITO-glass substrate, the cleaning agents are acetone, ethanol and isopropanol, the ultrasonic cleaning time is 10-30 minutes, and the oxygen plasma treatment time is 3 minutes.

3. The method for preparing a polarized organic electroluminescent device based on a two-dimensional elliptical metal nanorod lattice structured electrode according to claim 1, characterized in that: In step S2, the electron beam resist is polymethyl methacrylate, and the heating curing temperature is 150° C. and the curing time is 3 minutes.

4. The method for preparing a polarized organic electroluminescent device based on a two-dimensional elliptical metal nanorod lattice structured electrode according to claim 1, characterized in that: In step S2, the two-dimensional elliptical metal nanorod lattice structure prepared by the electron beam lithography system has a period of 310 nm, a short axis radius fixed at 30 nm, and long axis radii of 45, 60, 75, and 100 nm respectively.

5. The method for preparing a polarized organic electroluminescent device based on a two-dimensional elliptical metal nanorod lattice structured electrode according to claim 1, characterized in that: In step S2, the developer is a mixed solution of methyl isobutyl ketone and isopropyl alcohol in a volume ratio of 1:2, the fixer is an isopropyl alcohol solution, the developing time is 3 minutes, the fixing time is 1 minute, and the residual electron beam resist is removed using an acetone solution for 20 minutes.

6. The method for preparing a polarized organic electroluminescent device based on a two-dimensional elliptical metal nanorod lattice structured electrode according to claim 1, characterized in that: In step S3, the hole transport layer is one of 4,4'-cyclohexylbis[N,N-di(4-methylphenyl)aniline], N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine, the electron transport layer is one of 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene, 4,7-diphenyl-1,10-phenanthroline, 3,3'-[5'-[3-(3-pyridyl)phenyl][1,1':3',1"-terphenyl]-3,3"-diyl]dipyridine, the hole injection layer is MoO3, and the cathode is a Ca and Ag composite electrode.

7. The method for preparing a polarized organic electroluminescent device based on a two-dimensional elliptical metal nanorod lattice structured electrode according to claim 1, characterized in that: In step S3, the light-emitting layer is a red organic light-emitting material and a main material. The red organic light-emitting material is bis(2-methyldibenzo[F,H]quinoxaline)(acetylacetonate)iridium(III), and the main material is 4,4'-bis(N-carbazole)-1,1'-biphenyl and 1,3-bis(N-carbazolyl)benzene. The red organic light-emitting material is doped in the main material at a mass ratio of 8% to prepare an organic phosphorescent film as the light-emitting layer.

8. A polarized organic electroluminescent device based on a two-dimensional elliptical metal nanorod lattice structured electrode, characterized by: It is prepared according to the preparation method according to any one of claims 1 to 7.